ORTHODONTIC PAIN- CAUSES AND MANAGEMENT - P. , Kuzhalvaimozhi; Naveen,; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Orthodontic pain, the most cited negative effect arising as a result of orthodontic force application, is a major matter of distress for clinicians and patients/parents and directly influences their compliance during the treatment. The lengthy duration of treatment along with frequent pain due to the orthodontic appliances often leads to patient burnout and has been associated with discontinuation of orthodontic treatment. It is imperative for the clinicians to identify and manage the pain experienced by their patients. It becomes the duty of an orthodontist to satisfy the questions arising in the minds of patients, parents, and clinicians. Various modalities for the management of orthodontic pain have been proposed over the years. Aim of this review article is to throw a light on various causes of orthodontic pain and also about the recent advances in management of orthodontic pain